2017
DOI: 10.1186/s12890-017-0524-1
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MALAT1 protects preterm infants with bronchopulmonary dysplasia by inhibiting cell apoptosis

Abstract: BackgroundBronchopulmonary dysplasia (BPD) is a neonatal chronic lung disease characterized by impaired pulmonary alveolar development in preterm infants. Until now, little is known about the molecular and cellular basis of BPD. There is increasing evidence that lncRNAs regulate cell proliferation and apoptosis during lung organogenesis. The potential role of lncRNAs in the pathogenesis of BPD is unclear. This study aims to clarify the role of MALAT1 during the process of BPD in preterm infants and illustrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
(27 reference statements)
1
34
1
Order By: Relevance
“…Silencing of MALAT1 suppresses the activation of several factors including JNK1, overexpressed MALAT1 results in their phosphorylation, 28 and MALAT1 could regulate or influence the activity and expression of p53 in disease related to lung 29, 30. Additionally, MALAT1 overexpression suppressed cell apoptosis in bronchopulmonary dysplasia 31 . All of these findings, together with the results in the present study, suggested that MALAT1 and IL-8 were involved in LTIR injury, and aberrant expression of MALAT1 could regulate cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Silencing of MALAT1 suppresses the activation of several factors including JNK1, overexpressed MALAT1 results in their phosphorylation, 28 and MALAT1 could regulate or influence the activity and expression of p53 in disease related to lung 29, 30. Additionally, MALAT1 overexpression suppressed cell apoptosis in bronchopulmonary dysplasia 31 . All of these findings, together with the results in the present study, suggested that MALAT1 and IL-8 were involved in LTIR injury, and aberrant expression of MALAT1 could regulate cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings have confirmed that many lncRNAs have important roles in lung cancers. Two well-known lncRNAs, MALAT1 and HOTAIR, have been shown to regulate tumorigenesis and metastasis of NSCLC in many reports 38 – 40 . In addition, increasingly more lncRNAs have been found to regulate the proliferation of A549 cells 41 – 43 .…”
Section: Discussionmentioning
confidence: 99%
“…28 Long non-coding RNA MALAT1 alleviates the BPD in preterm infants by promoting cell proliferation and inhibiting cell apoptosis. 29 Supplementation of glutamine protects against BPD by increasing the cell viability and decreasing the cell apoptosis of hyperoxia-induced A549 cells. 30 In this study, up-regulation of CDC2 enhanced the cell viability and attenuated the cell apoptosis of hyperoxia-induced A549 cells.…”
Section: Discussionmentioning
confidence: 99%